Meta-Analisis Efektifitas Penggunaan E-Learning dalam Meningkatkan Pemahaman Konsep Fisika - Damayanti, Senia; Anggraini, Zunita Dwi; Setiaji, Bayu (Indonesian Journal Publisher, 2023)
It is seen that the development of information and communication technology has now penetrated into various sectors, one of which is in the field of education, especially in learning practices. The application of technology in the learning process, especially physics learning using e-learning, is expected to help students understand the material in physics. This study aims to determine the effectiveness of using e-learning media to understand physics concepts. In achieving the objectives in this study we conducted research using meta-analysis by reviewing 18 articles from two journals namely Scopus and Eric by filtering the two journals using the keywords e-learning, physics, and experiment. In this study the variables used in analyzing articles based on the type or model of e-learning and the material used in analyzing the effectiveness of e-learning. The results of this study show the overall effectiveness of the summary effect of 56%. The results also show that the most effective e-learning model or type is E-LMS and Blanded learning with a summary effect of 71% and for the material analyzed in this study the most effective material used is Mechanics with a large summary effect of 47%.